PERAMALAN DATA IHSG 2021-2025 DI INDONESIA DENGAN TIME SERIES MODELING AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Gempati, Abel; Faisal Agymnastiar Rahmad Fradani; Rayya Malik Ibrahim; Tenry Kusuma Astuti; Yusuf Riyan Prasetyo; Laksmi Yustika Devi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The real-time and fluctuating movements of the Indonesian Stock Exchange Composite Stock Price Index (Composite Stock Price Index) are often used by stakeholders, especially investors, as a reference in making investment decisions. This research aims to predict the Indonesian Stock Exchange Composite Stock Price Index (IDX Composite Index) using the Autoregressive Integrated Moving Average (ARIMA) time series model. Based on the results of research that has been carried out, the ARIMA model chosen is ARIMA 1 1 1. Therefore, by using this model forecasts can be made for ten weeks.